(untitled) (Jurnal Psikologi Udayana, 2025)
Self-harm is the act of intentionally harming oneself to express negative emotions in order to cope with emotional distress without the intention of committing suicide. The development of technology and social media has influenced the psychological development of adolescents. Doomscrolling is the compulsive and excessive consumption of negative news on social media. This study was conducted to investigate the relationship between Doomscrolling and Self-harmamong adolescents in Banjarmasin. The research method employed a quantitative approach with a correlational design. The research instruments used in this study were the Doomscrolling scale and the Self-harm Inventory. The sampling technique employed purposive sampling, with a sample size of 200 adolescent respondents aged 12–21 years in Banjarmasin. The results of the correlation test using Pearson’s r were 0.558 (ρ < 0.001), indicating a significant positive correlation between Doomscrolling and Self-harm among adolescents in Banjarmasin. It can be concluded that Doomscrolling has the potential to be a risk factor for increasing selfharm. This study is expected to enrich empirical references and serve as a basis for further research.